Changes in hospital and out-patient events and costs following implant naltrexone treatment for problematic alcohol use - Kelty, E.; Hayes, L.; O'Neil, G.; Kyle, S.; Jeffrey, G.; O'Neil, G.; Hendrie, Delia; Mukhtar, Syed Aqif; Hulse, G. (Sage Publications, 2014)
The harmful use of alcohol places a considerable burden on the community, both socially and financially. The aim of this study was to determine if the use of implant naltrexone is associated with a reduction in health care events and costs in patients treated for problematic alcohol use. Ninety four patients (60.6% male) treated between 2002 and 2007 were matched against state hospital, emergency department (ED), mental health out-patients and mortality data sets for 6 months prior to and 6 months post treatment. The number of patients, events, and costs associated with each health event were compared before and after treatment. Overall health care events and costs were reduced from $509033 prior to treatment to $270001 following treatment. Costs associated with hospital admission showed the most significant reduction, falling from $424605 (82 admissions/36 patients) before treatment to $203462 (43 admission/24 patients) after. While costs associated with ED attendances also fell ($74885 to $54712), costs associated with mental health out-patient attendances increased ($9543 to $11827). The use of implant naltrexone was associated with a reduction health events and costs in patients with problematic alcohol use in the first 6 months following treatment.